Implementation of Digital-Based Media in PAIBP Subjects in Improving Student Literacy at SMKF YPIB Kedawung Cirebon - Hasan Nurdin; Imam Tabroni; Ahmad A. Khozim (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2025)
Literacy is a crucial aspect of education, particularly in the digital era. This research is motivated by the current challenges faced in Indonesian schools, namely the low level of students’ critical thinking skills. Along with the rapid development of digital technology, the challenges related to literacy are becoming increasingly significant. The purpose of this study is to explore the innovation of implementing digital-based media to enhance literacy at SMK Farmasi YPIB, Kedawung District, Cirebon Regency. Specifically, it aims to investigate the process of planning, implementation, evaluation, as well as the strengths and obstacles encountered during the implementation process. This research employs a qualitative method with a naturalistic descriptive approach, by describing the data in accordance with the activities occurring in the field. In interpreting this naturalistic research, the researcher conducted an in-depth and comprehensive investigation of various activities taking place during the learning process. The findings reveal that the implementation process was highly structured, as evidenced by careful planning, which included preparing lesson plans (RPP), uploading materials prior to classroom sessions, and designing innovative teaching media. The learning implementation became more interactive, encouraging students to engage in critical thinking when analyzing relevant information through assigned analytical tasks. In conclusion, the implementation of digital-based media in PAIB subjects for grade XI students at SMK Farmasi YPIB, Kedawung District, Cirebon, proved effective in improving students’ literacy. This was demonstrated by students’ active participation in learning. However, literacy levels remain relatively limited due to several factors that require greater emphasis and optimization, particularly in fostering consistent habits of utilizing digital media.